Wydział Teologiczny Sekcja w Tarnowie Papieskiej Akademii Teologicznej w Krakowie - Żurek, Antoni (Studia Nauk Teologicznych PAN, 2020)
Th e Department of Th eology Section in Tarnów was established formally as a result of transformation of Th e Institute of Th eology in Tarnów. Th is Institute was founded in 1822 for educating the clergy serving Tarnów diocese and its activities were always strongly connected to the Seminary in Tarnów. Since the communists took control over our country in 1945, the Institute existed only formally, but in fact, it was always identifi ed with Th e Seminary in Tarnów. Bishop professor habilitated doctor Józef Życiński, who was at that time the Tarnów bishop, transformed the Institute of Th eology into the Th eology and Pastoral Institute and strongly contributed to its aggregation to the Th eology Department of the Pontifi cal Academy of Th ology in Kraków in 1993. Since then, the graduates of the Institute have had the opportunity to obtain the MA degree in theology. Th anks to eff orts of bishop doctor Wiktor Skworc, the Congregation of the Catholic Education established the Department of Th eology Section in Tarnów of the Pontifi cal Academy of Th ology in Kraków (WTST) instead of the Institute. In 2007 the Department of Th eology Section in Tarnów obtained the rights to confer a PhD degree in theology. Since the aggregation of the Institute of Theology Section in Tarnów to the Theology Department of the Pontifical Academy of Th ology, about 90 to 100 students receive their MA degrees annually. Approximately, half of this group consists of the secular and another half of the monastic. Since the beginning, the number of secular candidates accepted, has always been limited. There are the following profiles to choose from: sacerdotal, pastoral and catechetical, social and charity.